One-year outcome of patients admitted after cardiac arrest compared to other causes of ICU admission. An ancillary analysis of the observational prospective and multicentric FROG-ICU study. (1st January 2020) - Kimmoun, Antoine; Cariou, Alain; Gayat, Etienne; Feliot, Elodie; Takagi, Koji; Megarbane, Bruno; Mebazaa, Alexandre; Deye, Nicolas; ,
Abstract: Objective: While cardiac arrest (CA) patients discharged alive from intensive care unit (ICU) are considered to have good one-year survival but potential neurological impairment, comparisons with other ICU sub-populations non-admitted for CA purpose are still lacking. This study aimed to compare long-term outcome and health-related quality of life (HRQOL) between CA patients and patients admitted to ICU for all other causes. Methods: In 1635 patients discharged alive from 21 European ICUs in an ancillary analysis of a prospective multicentric cohort, we compared CA causes of ICU admission to all other causes of ICU admissions (named non-CAs). The primary endpoint was one-year survival rate after ICU discharge. Secondary endpoints included HRQOL at 3, 6 and 12 months after ICU discharge using the outcome survey short form‐36 (SF36). Propensity score matching was used to consider the probability of having CA. Results: Of the 1635 patients, 1561 were included in this study comprised of 1447 non-CAs and 114 CAs. At one-year in the non-matched population, survival rate was greater in the CA group 89% versus the non-CA group 78% (log rank p = 0.0056). In the matched population, this difference persisted between CAs and non-CAs (log rank p = 0.049). The physical component summary of the SF36 scale was higher in the CA group than in the non-CA group at all time points in both non-matched and matched populations. Conclusions: CA patients discharged alive from ICU have a better one-year survival and a better HRQOL specifically on physical functions than patients admitted to ICU for other causes. Trial registration: ClinicalTrials.gov NCT01367093; registered on June 6, 2011.